A sziléziai Vajdaság gazdaságfejlesztése - Nagyházi, György (Közép-Európai Közlemények, 2011)
The Silesian Voivodship is the most industrialized region of Poland, which has been characterized by the traditional heavy industry and mining throughout its modern age history. This paper is aiming to examine on the one hand, that what kind of economic developmental tools have been used by the local governments and the central government, in order to facilitate the industrial restructuring of the region after the democratic changes. The question is that how far these have been successful. Integral part of the paper is the examination of the transformation of the public administration and the local governmental system in Poland, especially the formation of the Voivodships and their competencies. The main sources of the paper are the Territorial Review of Poland by the OECD, and the Regional Strategy of the Silesian Voivodship, apart from other relevant publications, such as the report of the Central Statistical Office of Poland. The aim of the paper is to establish, that which policy tools were the most effective in revitalizing the region’s economy.